Estudio de métodos y tiempos dentro del proceso medida especial en la empresa Applus Norcontrol Sede Santa Marta (2020)
This research work determines the procedures on how a study of methods and times was carried out in order to identify the time spent in the development of the activities that were the object of study in the Applus Norcontrol company in the process of Special Measure headquarters Santa Marta. Carrying out a study of methods and times is of utmost importance for any organization where there are production processes related to people, raw materials and facilities, with the possibility of improving productivity with the application of methods, standards and work design. . The study of methods and times consisted of analyzing the situation in which the company was through the analysis of management indicators, working methods and identification of bottlenecks, in this way modifications were proposed and established in the execution of the activities that were objects of study, later a series of trainings was carried out on the critical phases that were found. Next, a comparison of the times before and after the established improvements was made and an average reduction in the execution time of 38,55% was observed, and then the implementation of improvement techniques in the process was sought.